2016
DOI: 10.1021/acs.jafc.6b02751
|View full text |Cite
|
Sign up to set email alerts
|

Site Directed Mutagenesis of Dextransucrase DsrM from Weissella cibaria: Transformation to a Reuteransucrase

Abstract: Glucansucrases produce α-glucans and gluco-oligosaccharides; the linkage type and molecular weight of glucans impacts their functionality. This study compared the catalytic specificities of dextransucrase DsrM from Weissella cibaria 10M and derivatives of this enzymes with GtfA from Lactobacillus reuteri TMW1.656. The N-variable region, which is dispensable for GtfA activity, was essential for DsrM activity. Parallel amino acid substitutions in DsrM-ΔS and GtfA-ΔN indicated that the acceptor binding site resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Substitutions of the same tripeptide by different motifs such as NNA, YNA, YDA in GTF180 also resulted in slight modulation of α-1,3/α-1,6 linkage specificity and variation of α-1,4 linkage content in the polymers [ 193 ]. The NNS mutant of DsrM from Weissella cibaria 10M remarkably produced a reuteran polymer with 52% and 48% of α-1,4 linkages and α-1,6 linkage whereas the parental enzyme synthesized a dextran with only 2% of α-1,4 branching linkages [ 195 ]. Targeting the same regions in reuteransucrase GTFA also decreased the α-1,4/α-1,6 ratio changing the reuteransucrase into a dextransucrase [ 196 ].…”
Section: Enzyme Engineering For Man-made α-Glucans Oligosaccharides and Glucoconjugatesmentioning
confidence: 99%
“…Substitutions of the same tripeptide by different motifs such as NNA, YNA, YDA in GTF180 also resulted in slight modulation of α-1,3/α-1,6 linkage specificity and variation of α-1,4 linkage content in the polymers [ 193 ]. The NNS mutant of DsrM from Weissella cibaria 10M remarkably produced a reuteran polymer with 52% and 48% of α-1,4 linkages and α-1,6 linkage whereas the parental enzyme synthesized a dextran with only 2% of α-1,4 branching linkages [ 195 ]. Targeting the same regions in reuteransucrase GTFA also decreased the α-1,4/α-1,6 ratio changing the reuteransucrase into a dextransucrase [ 196 ].…”
Section: Enzyme Engineering For Man-made α-Glucans Oligosaccharides and Glucoconjugatesmentioning
confidence: 99%
“…For GSs, enzyme engineering studies and the availability of 3D structures demonstrated that their product specificity is determined by the interplay of various amino acid residues shaping the acceptor binding subsites (Meng et al, 2016c). This makes it difficult to predict the effect of single mutations, even more so because it may differ between GSs of different sources (Chen and Ganzle, 2016). Mutations may also lead to changes in more than one structural feature of the product, and/or affect the enzyme transglycosylation activity (Hellmuth et al, 2008;Meng et al, 2014Meng et al, , 2016a.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations resulting in the production of polysaccharides with reduced or increased molecular masses also have been reported (van Leeuwen et al, 2009;Irague et al, 2012;Meng et al, 2014;Chen and Ganzle, 2016;Meng et al, 2015a), although the structural determinants of α-glucan product size are not fully understood. Mutagenesis of some of the + 1 and + 2 acceptor binding residues significantly affected the ratio of polysaccharide versus oligosaccharide synthesis by reducing or increasing the affinity of the enzyme for the growing acceptor substrate chain (Kralj et al, 2005b(Kralj et al, , 2006Moulis et al, 2006;Hellmuth et al, 2008;Meng et al, 2014Meng et al, , 2016b.…”
Section: )mentioning
confidence: 99%